Manganese Crust Project, Hawaii - An Update Of Progress And Plans - Charles L. Morgan (International Marine Minerals Society, 1985)
The Minerals Management Service of the U.S. Department of the Interior and the State of Hawaii Department of Planning and Economic Development are investigating the cobalt-rich ferromanganese oxide crust deposits found within the Exclusive Economic Zones (EEZ) of the Hawaiian Islands and Johnston Atoll. The objective of this investigation is to complete a preliminary resource assessment and an Environmental Impact Statement for potential leasing of mineral rights to these crusts. The results of this effort will be summarized and published in a Draft Environmental Impact Statement in March 1986. Three oceanographic cruises to deposit sites in the Hawaiian Islands EEZ were conducted by the University of Hawaii in 1984. As a result, data and sample analysis yielded the following resource estimates (in thousand tonnes): (1) total crusts - 378,500; (2) cobalt - 2,500; (3) manganese - 76,200; (4) iron - 59,700; and (5) nickel - 1,400. These estimates do not include key factors such as deposit continuity, recoverability, and environmental sensitivity. A preliminary attempt to quantify some of these factors for one particular deposit is in progress and will consist of detailed field studies followed by laboratory analysis. Similar evaluations of the Johnston Island EEZ have also begun and are based upon field work conducted by West German researchers and the U.S. Geological Survey. The Johnston Island EEZ appears to have crust resources about as large as those contained in the entire Hawaiian EEZ.